Delivering Research-Based Professional Development to Adult Educators: Innovative Online Options - Catherine Green (Adult Education Research Conference, 2010)
Research demonstrates that an effective means of improving learner outcomes is by supporting instructors with professional development (PD), preferably job-embedded. Yet in California, the challenges of providing professional development to adult literacy providers are myriad and include funding issues, lack of job security, lack of adequate teacher preparation, etc. In light of these and other challenges, this paper highlights several innovative techniques used to deliver research-based PD to adult educators online.